Estudo de modelos experimentais aplicáveis à seleção de combinações de fármacos em avaliações pré-clínicas da doença de chagas - Raimundo, Breno Vilas Boas (2019)
Although many advances have been made in the field of Chagas disease chemotherapy in recent years, there is still no treatment with a satisfactory efficacy and safety profile for the chronic phase of Trypanosoma cruzi infection. Repositioning and drug combination have been highlighted as promising strategies in the search for new therapies. However, in parallel with the search for new alternatives, it is necessary to improve existing preclinical evaluation models. In this sense, the aim of the present study was to evaluate the effects of ravuconazole in combination with amiodarone on the development of acute T. cruzi infection in different experimental models. Initially, in vitro experiments were performed to determine the toxicity of the combination and the nature of the drugs on the infection of H9c2 cells by Y strain of T. cruzi. Subsequently, in vivo experiments were performed using different lineages of mice (Swiss and BALB/c) and strains of the parasite that show varying degrees of resistance to etiological treatment (Y and Colombian). The infected animals were treated from the 5th (strain Y) or 10th (Colombian strain) day after infection for 5 days orally with ravuconazole (0.5mg/kg) and amiodarone (50mg/kg) alone and in combination. Uninfected control group, infected and untreated group, infected and treated with ravuconazole at 10mg/kg or benznidazole at the dose of 100mg / kg were also included. The parasitemia was quantified daily during the whole period of the experiment. Five days after the end of treatment the animals were euthanized and the heart collected for histological analysis. The obtained results allowed to confirm the trypanosomicidal activity of the drugs and to identify additive effect resulting from the combination between amiodarone and ravuconazole in vitro, in the absence of additional toxicity. In vivo, amiodarone was not efficient in controlling infection by different strains of the parasite, whereas the effect of ravuconazole on Y strain was dependent on the dose and mouse strain used; while at 10 mg/kg azole suppressed the parasitemia of Y strain infected animals in both strains, the effect of underdose on parasitism control was significantly lower in BALB/c. On the other hand, combined therapy was effective in reducing the area under the parasitemia curve compared to monotherapies, regardless of mouse strain, suggesting a positive interaction between drugs. Interestingly, ravuconazole underdose drastically reduced parasitemia in mice infected with the Colombian strain while the combination did not induce additional benefit. Histopathological evaluation of cardiac muscle tissue showed that the combined use of ravuconazole and amiodarone, unlike monotherapy at the same doses, mitigated the damage caused by infection, regardless of the parasite strain or host lineage. The data obtained allow to conclude that the experimental strategy adopted was efficient to evaluate the interaction between drugs and suggest that the BALB/c lineage is a more stringent model for preclinical studies in Chagas disease chemotherapy. In addition, ravuconazole and amiodarone combined have a superior effect than monotherapies in reducing parasitism and preventing heart damage due to infection.